The Protective Effect of Low-Dose Ethanol on Myocardial Fibrosis through Downregulating the JNK Signaling Pathway in Diabetic Rats - Ying Yu; Xian-Jie Jia; Wei-ping Zhang; Ting-ting Fang; Jie Hu; Shan-Feng Ma; Qin Gao (Journal of Diabetes Research)
Objective. To investigate the effects of low dose ethanol feeding in diabetic rats and analyze its underlying mechanisms. Methods. Male Sprague-Dawley rats were divided into 4 groups: control (Con), diabetes at 4 weeks (DM4W), diabetes at 8 weeks (DM8W), and EtOH + DM8W. After 8 weeks, hemodynamic parameters were recorded and heart weight/body weight (H/B) and hydroxyproline (Hp) content in myocardium were measured. Morphology of collagen in myocardial tissue was observed with Masson’s trichrome staining method and collagen volume fraction (CVF) was analysed. The mRNA expression of ALDH2 was assessed with Real-Time PCR. The protein expressions of p-JNK and JNK were evaluated using western blot. Results. In contrast to Con group, there was no difference in hemodynamic parameters in DM4W group, but mean arterial pressure and heart rate were decreased in DM8W group, and the ratios of H/B, Hp, and CVF were markedly increased. ALDH2 mRNA expression was decreased, while the ratio of p-JNK/JNK were increased. Compared with DM8W group, the above indexes were improved in EtOH + DM8W group. Conclusion. With low dose ethanol intervention, enhanced ALDH2 expression can antagonize the happening of myocardial fibrosis in diabetic rats, which may be relevant with downregulating the JNK pathway.